SISTEM PENGAMBILAN KEPUTUSAN KEPUASAN MUTU SEKOLAH DENGAN METODE PROFILE MATCHING - Sopiyan Dalis; Syamsul Bahri; Rahman Tuah Damanik (INTI Nusa Mandiri, 2020)
SMA Kanaan Global School is a private school in Jakarta which has many achievements both in academic and non-academic terms including in the quality of the school. It cannot be separated from the use of even more information that is needed to always advance and develop in order to support the quality of school quality. For this reason, the writer tries to make a thesis on the assessment of school quality satisfaction at SMA Kanaan Global School Jakarta. This school itself is moving to improve quality towards national standard schools plus so that it is at the forefront of global competition. By more actively improving the quality of education and improving teacher qualifications, as well as increasing the average grade of passing national examinations to become one of the best and satisfying schools. In processing the data the author uses the profile matching method. the final results obtained by the author of the satisfaction of high school quality Kanaan Global School Jakarta Jakarta is "PUAS" with an assessment range of 3.6 - 4.5 as many as 37 respondents.